A Rare Case of Compression Neuritis due to Intraorbital Arteriovenous Fistula (IOAVF) Mimicking Retrobulbar Optic Neuritis - Minakawa, Shun; Hirano, Masayuki; Takahashi, Kazuya; Imamura, Yuta; Watanabe, Takashi (Acta medica Okayama, 2025)
Intraorbital arteriovenous fistulas (IOAVFs) are rare vascular abnormalities. We describe a case of an IOAVF featuring a direct shunt between the accessory meningeal artery and the superior ophthalmic artery. A 55-year-old woman presented with a 1-month history of visual impairment in her right eye, and magnetic resonance imaging (MRI) revealed optic neuritis-like findings. Steroid pulse therapy temporarily resolved visual impairment. However, 1 month later, she experienced decreased visual acuity, ocular conjunctival hyperemia, edema, and a pulsatile murmur. Contrast-enhanced MRI and digital subtraction angiography revealed compression optic neuropathy due to an IOAVF. Following successful treatment with transarterial embolization, her symptoms disappeared.